1993
DOI: 10.1128/jvi.67.10.6000-6014.1993
|View full text |Cite
|
Sign up to set email alerts
|

DNA-binding domain of bovine papillomavirus type 1 E1 helicase: structural and functional aspects

Abstract: The El protein of bovine papillomavirus type 1 is a multifunctional enzyme required for papillomaviral DNA replication. It assists in the initiation of replication both as a site-specific DNA-binding protein and as a DNA helicase. Previous work has indicated that at limiting El concentrations, the E2 protein is required for efficient El binding to the replication origin. In this study, we have defined the domain of the El protein required for site-specific DNA binding. Experiments with a series of truncated pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
60
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 43 publications
7
60
0
Order By: Relevance
“…The carboxy-terminal boundary that we determined is consistent with the previous observation that an E1 1-299 protein retained origin binding activity (15) but is in contrast to the recent results of Sarafi and McBride that an E1 1-328 protein lacked origin binding activity (12). Furthermore, Sarafi and McBride showed that an E1 1-378 and an E1 162-422 protein bound the origin but that an E1 162-378 protein did not (12).…”
supporting
confidence: 89%
See 2 more Smart Citations
“…The carboxy-terminal boundary that we determined is consistent with the previous observation that an E1 1-299 protein retained origin binding activity (15) but is in contrast to the recent results of Sarafi and McBride that an E1 1-328 protein lacked origin binding activity (12). Furthermore, Sarafi and McBride showed that an E1 1-378 and an E1 162-422 protein bound the origin but that an E1 162-378 protein did not (12).…”
supporting
confidence: 89%
“…In vitro, E1 alone is sufficient to initiate replication (3), but in vivo the viral full-length E2 transcriptional activator protein is also absolutely required (16). E1 can form complexes with the E2 protein (2,8,15,20), and both binding to and unwinding of origin DNA by E1 is enhanced by these cooperative interactions with E2 (4,9,13,20). Consequently, the replication function of E1 appears dependent upon both protein-DNA and protein-protein contacts.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The binding site of E2 on the E l molecule has been mapped to amino acids 384-516 (Lusky and Fontane, 1991) and amino acids 458-605 (Thorner et al, 1993) of BPV1. In HPV11, preliminary data localised the site of complex formation to a region of the E l protein before amino acid 251 (Bream et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…The bovine papillomavirus (BPV) genome encodes two proteins that are essential for viral DNA replication . The El protein is a 72 kDa nuclear protein with a sequence-specific DNA binding activity that serves to recognize the ori, has DNA-dependent ATPase activity and can function as a DNA helicase Wilson and Ludes-Meyers, 1991;Yang et al, 1991;Holt et al, 1993;Seo et al, 1993a; ( Oxford University Press Thorner et al, 1993;Yang et al, 1993). The E2 protein functions as a sequence-specific activator of transcription (Spalholz et al, 1985;Androphy et al, 1987;McBride et al, 1991), but is also required for viral DNA replication.…”
Section: Introductionmentioning
confidence: 99%